Blockchain-Based E-Voting System: A Decentralized Approach on the Ethereum Private Network - Syaifudin, Yan Watequlis; Prada Aprilia, Silvia; Apriliyanto, Salies; Rizqiyatul Himmah , Dinda; Siradjuddin, Indrazno; Sinal, Mohammad; Aulia Rahmadani, Alfiandi (International Journal of Frontier Technology and Engineering, 2024)
The e-voting system, which is based on blockchain technology, greatly improves the security, transparency, and integrity of electronic voting. This is achieved by using a decentralized ledger system that distributes the recording of votes, allows for public verification, and maintains voter anonymity through cryptographic methods. This resilient method guarantees that once a vote is submitted, it is securely recorded and cannot be changed without the agreement of network members, thereby protecting the integrity of elections. Built on the private Go Ethereum (Geth) network, this study implements an e-voting system that features validator nodes for transaction verification, user-friendly mobile applications for voter interaction, and comprehensive smart contract capabilities that define the voting process rules. The mobile application guides users from launching the app and authenticating their identity to selecting candidates and securely recording their votes, ensuring seamless connectivity to the blockchain and incorporating essential verification steps. Furthermore, the implementation process includes meticulous setup of Ethereum nodes, smart contract development, and thorough testing for functionality, performance, and security. The evaluation focuses on aspects like maintaining data transparency, user authentication, and resilience against unauthorized access, demonstrating high user satisfaction with the app's performance. Ultimately, this blockchain-based system addresses modern electoral challenges, ensuring a secure, transparent, and reliable voting experience that fosters trust among all stakeholders involved.